The impact of resource misallocation on green technology innovation: evidence from 288 cities in China - Huiping Wang; Xinge Guo (Humanities & Social Sciences Communications)
Abstract Resource misallocation, as a key characteristic of China’s ongoing reform process, has emerged as a significant barrier to high-quality economic development. This paper discusses the impact of capital and labor misallocation on green technology innovation (GTI) from the resource allocation perspective. The panel data of 288 Chinese cities from 2009 to 2022 are used to empirically test the effects of capital misallocation and labor misallocation on GTI and to further analyze urban heterogeneity and the moderating effect of environmental regulation. The study reveals that there is an inverted U-shaped relationship between resource misallocation and GTI. That is, a slight misallocation of capital and labor due to market mechanisms and government regulations has a promoting effect on GTI. However, when misallocation reaches a certain level, it significantly inhibits GTI. In eastern China, the capital misallocation’s impact on GTI is more significant, while in central and western China, the labor misallocation’s on GTI is more significant. Only in small cities is there an inverted U-shaped relationship between labor misallocation and GTI. In non-resource cities, a reversed U-shaped pattern emerges between capital misallocation and GTI, whereas in resource cities, the two exhibit a U-shaped relationship. Environmental regulation can strengthen the inverted U-shaped relationship between capital misallocation and GTI.